Nurse–Patient Interaction as a Treatment for Antepartum Depression: A Mixed-Methods Analysis. (September 2017) - Evans, Emily C.; Deutsch, Nancy L.; Drake, Emily; Bullock, Linda
BACKGROUND: The U.S. Preventative Services Task Force guidelines recommend pregnant women be screened for depression and adequate systems be in place to treat this condition.OBJECTIVE: This study examines a nurse-delivered telephone support intervention provided to low-income, pregnant women living in rural settings.DESIGN: This study had a complementary mixed-methods design, using secondary data. Peplau's theory of interpersonal relations was used as a framework to guide the study.RESULTS: The phases of Peplau's theory of interpersonal relations were evident in the interactions. Underserved women at high risk for depression appreciated this type of support, with the women at highest risk for depression utilizing more of the nursing support provided. On average, Mental Health Index–5 scores improved from 45 to 66.CONCLUSION: A nurse-delivered telephone support intervention, modeled around Peplau's theory of interpersonal relations, may be an effective way of providing support to underserved women and has the potential to treat or offset antepartum depression.